Large effect life-history genomic regions are associated with functional morphological traits in Atlantic salmon - Aykanat, Tutku; Debes, Paul V; Jansouz, Shadi; Gueguen, Lison; House, Andrew H; Ruokolainen, Annukka; Erkinaro, Jaakko; Pritchard, Victoria L; Primmer, Craig R; Bolstad, Geir H (Oxford University Press, 2025)
Understanding pleiotropic architectures of phenotypes is instrumental for identifying the functional basis of adaptive genetic variation in the wild. Life-history variation may have a morphological basis that mediates resource acquisition allocation pathways, but identifying the underlying genetic basis of such traits is challenging. Using Atlantic salmon (Salmo salar) juveniles reared in common garden conditions, we test if 2 life-history associated loci, six6 and vgll3, are also associated with functional morphological traits. These loci had previously shown to exhibit strong signals of adaptation and are highly correlated with sea age at maturity. We show that genetic variation at the vgll3 locus is linked to variation in morphological traits that underlie swimming performance, along a tradeoff axis between efficient cruising and maneuvering, while the genetic variation at the six6 locus was linked to variation in body-head proportions suggesting the potential functional importance of these traits for resource acquisition efficiency. However, the direction of changes in morphological traits associated with late- vs early maturing alleles was not always consistent with the expected direction of an effect to maturation timing. Our results reveal a complex morphological landscape associated with the genetic variation in these loci, possibly as a result of pleiotropy or linkage across these genomic regions.
Keywords: Atlantic salmon; morphology; morphometrics; adaptive genetic variation; age at maturity; pleiotropy; six6; vgll3